Dog erythrocyte antigens (DEA) 1, 4, 7 and suspected naturally occurring anti-DEA 7 antibodies in Italian Corso dogs. (April 2017) - Spada, E.; Proverbio, D.; Priolo, V.; Ippolito, D.; Baggiani, L.; Perego, R.; Pennisi, M.G.
Highlights: Information on prevalence of dog erythrocyte antigens (DEAs) is important in selection of blood donors. Corso dogs fulfil common requirements for blood donors: large size, good-tempered, easy to handle during blood collection. There is a high prevalence of DEA 1 and DEA 7-negative dogs in the Corso breed. The presence of suspected naturally occurring anti-DEA 7 antibodies may be implicated in delayed transfusion reactions. Abstract: We sought to determine the prevalence of dog erythrocyte antigen (DEA) 1, 4 and 7 and naturally occurring anti-DEA7 antibodies in Italian Corso dogs. In addition, we correlated DEAs with different epidemiologic variables, compared the prevalence of DEAs against other canine populations and assessed the risk of sensitisation and transfusion reactions (TRs) following unmatched transfusion. Blood samples from 100 Corso dogs were evaluated for DEA 1, 4, 7 and naturally occurring anti-DEA 7 antibodies. Seventy-one percent of samples were DEA 1-negative, 100% tested DEA 4-positive, and 95% tested DEA 7-negative. Suspected anti-DEA7 antibodies were found in 32% dogs. The DEA 1 and 7-negative phenotypes were significantly more common than in most canine populations. When a previously tested Italian canine population was considered as blood donors for Corso dogs, the risk of DEA 1 sensitisation using DEA 1 untyped blood was 29%, and of acute haemolytic TRs after a second untyped DEA 1-incompatible transfusion was 8%. The potential for delayed TRs between DEA 7-negative Corso dogs with suspected naturally occurring anti-DEA 7 antibodies receiving untyped DEA 7-positive blood was 11%. Conversely, when Corso dogs were blood donors for the same population, the risk of DEA 1 sensitisation was 17% and the risk of an acute haemolytic TR after a second DEA 1-incompatible blood transfusion was 3%. Corso dogs can be suitable blood donors. Additional studies are needed to clarify whether the high prevalence of naturally occurring anti-DEA 7 antibodies in this breed could increase their risk of delayed TRs when they are blood recipients.